Uridylation prevents 3′ trimming of oligoadenylated mRNAs - Sement, François Michaël (Oxford University Press, 2013)
Degradation of mRNAs is usually initiated by deadenylation, the shortening of long poly(A) tails to oligo(A) tails of 12–15 As. Deadenylation leads to decapping and to subsequent 5′ to 3′ degradation by XRN proteins, or alternatively 3′ to 5′ degradation by the exosome. Decapping can also be induced by uridylation as shown for the non-polyadenylated histone mRNAs in humans and for several mRNAs in Schizosaccharomyces pombe and Aspergillus nidulans. Here we report a novel role for uridylation in preventing 3′ trimming of oligoadenylated mRNAs in Arabidopsis. We show that oligo(A)-tailed mRNAs are uridylated by the cytosolic UTP:RNA uridylyltransferase URT1 and that URT1 has no major impact on mRNA degradation rates. However, in absence of uridylation, oligo(A) tails are trimmed, indicating that uridylation protects oligoadenylated mRNAs from 3′ ribonucleolytic attacks. This conclusion is further supported by an increase in 3′ truncated transcripts detected in urt1 mutants. We propose that preventing 3′ trimming of oligo(A)-tailed mRNAs by uridylation participates in establishing the 5′ to 3′ directionality of mRNA degradation. Importantly, uridylation prevents 3′ shortening of mRNAs associated with polysomes, suggesting that a key biological function of uridylation is to confer 5′ to 3′ polarity in case of co-translational mRNA decay.